Comparison of D2 and D2 plus radical surgery for advanced distal gastric cancer: a randomized controlled study - Pengfei Yu; Yian Du; Zhiyuan Xu; Ling Huang; Xiangdong Cheng (World Journal of Surgical Oncology, 2019)
Abstract Background The optimal extent of lymph node (LN) dissection for advanced distal gastric cancer remains controversial. The present study compared the safety and efficacy of extended LN dissection (D2 plus) with standard D2 radical surgery for advanced distal gastric cancer. Methods Eligible patients were enrolled and randomly assigned into two groups: D2 group and D2 plus group. Patients in the D2 group received standard D2 LN dissection, while patients in the D2 plus group received an additional nos. 8p, 12b, 13, and 14v LNs dissection. The clinicopathological and surgical data of these two groups were compared, and the factors that may influence survival were analyzed. Results Seventy patients were enrolled, out of which 64 patients were analyzed. There were no significant differences in the operative time, blood loss, and complications between the two groups. In the D2 plus group, the positive rate of the nos. 12b, 13, and 14v LN was 3.1%, 9.4%, and 12.5%, respectively. The positive rate of the no. 13 LN correlated with the duodenal involvement, while the positive rate of the no. 14v LN correlated with no. 6 LN metastasis. The survival analysis indicated that among patients with duodenum involvement, the 3-year disease-free survival rate of the D2 plus group was significantly better than that of the D2 group. Conclusion Duodenum involvement and positive no. 6 LN were high-risk factors of advanced distal gastric cancer. D2 plus radical surgery turned out to be safe and feasible, and may improve the prognosis of these patients. However, further clinical trials are still warranted. Trial registration This study is registered with ClinicalTrials.gov as NCT01836991, registered on 22 April 2013.